The Impact of Vitamin D Receptor Gene Polymorphisms and Haplotypes on the susceptibility to Toxoplasmosis - Qasim Sharhan Al-Mayah (Diyala Journal of Medicine, 2018)
Background: Toxoplasmosis is a cosmopolitan infectious disease caused by Toxoplasma gondii. Vitamin D is an immune modulator exerting its effect through a nuclear receptor called vitamin D receptor. Genetic polymorphisms in the vitamin D receptor gene could affect the activity of vitamin D and hence the individual’s susceptibility to toxoplasmosis.